Manajemen Perkantoran dalam Menciptakan Efektivitas Kinerja Karyawan Menurut William H. Leffingwell - Aulia Jannah; Sri Wahyuni; Erfiani Lubis; Ilham Martua Hasibuan; Tengku Darmansah (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
This research discusses office management in creating effective employee performance according to William H. Leffingwell. Office management is a series of activities to plan, manage, organize, direct, supervise the implementation of office work effectively and efficiently so as to achieve the expected goals. Office life will be well managed and run smoothly with all existing activities and programs, if the office applies management sciences to it. Management is needed, so that offices can be managed well, by making optimal use of existing infrastructure, organizing employees appropriately, arranging employee duties and responsibilities well, and evaluating the results of employee performance and the office's achievements. This research uses library research by collecting all data and information related to creating effective employee performance in office management through books and scientific articles that are relevant to the topic discussed.